A Service-Based Selfish Routing for Mobile Social Networks. (1st June 2015) - Yu, Lingfei; Liu, Pengfei
Abstract : Routing in mobile social networks is a challenging task due to the characteristic of intermittent connectivity, especially when the nodes behave selfishly in real world. Selfish behaviors of node always influence its altruism to provide forwarding service for others and degrade network performance strongly. In this paper, to address the selfishness problem in MSNs, we propose a service-based selfish routing protocol, SSR. When making forwarding decision, SSR employ user altruism and the amount of service that the relay nodes provide. User altruism is determined by the social selfishness and the individual selfishness. The services include pairwise services and social services, which is also considered as the incentives to stimulate node to be more cooperative. The more services the node provides, the more chance the node has to be served. The node with higher altruism and fewer services is the preferred relay node. Simulation results show SSR achieves better performance when the user altruism is low and demonstrate the effectiveness of the service-based scheme.